HRM Practices and Employee Satisfaction in Nepalese Commercial Banks - Ojha, Deepak; Ranabhat, Deepesh; Poudel, Samikshya (The Batuk, 2025)
This study examined the impact of human resource management practices on employee satisfaction in Nepalese commercial banks, focusing on training and development, performance appraisal, compensation, career planning, and decision-making practices. Employing a descriptive and causal-comparative research design, data was collected through structured questionnaires from 200 employees across 20 commercial banks in Pokhara Metropolitan City. Purposive sampling was used to target commercial banking employees, with responses analyzed using correlation and regression techniques. The findings indicate that employees have a positive perception toward different dimensions of human resource practices. Correlation analysis reveals strong interrelationships between HR practices, suggesting that improvements in one area are likely to benefit others. Regression analysis demonstrates a significant positive impact of employee involvement in decision-making, performance appraisal, and career development practices on employee satisfaction. This study concludes that enhancing decision-making, appraisal, and career development can improve employee satisfaction in Nepalese commercial banks.